Smart policing service quality: conceptualisation, development and validation. Issue 5 (10th August 2020) - Ekaabi, Maryam Ahmed; Khalid, Khalizani; Davidson, Ross; Kamarudin, Ahmad Haifeez; Preece, Christopher
Abstract : Purpose: This study evaluates a multidimensional hierarchical scale of smart policing service quality. Design/methodology/approach: Qualitative and quantitative analysis tools were used to develop a smart policing service quality scale based on the integrative psychometric scale development methodology. A multidimensional hierarchical structure was proposed for smart policing service quality; a group of preliminary items selected from literature was used for the qualitative analysis. For data collection, users of smart policing services were selected through the United Arab Emirates (UAE) research centre. Several statistical methods were employed to verify reliability and validity of the construct and nomological validity of the proposed scale. Findings: A smart policing service quality scale of 23 items was developed based on a hierarchical factor model structure. Nomological testing indicated that overall smart policing service quality is positive and significant, thus contributing to user satisfaction, intention to continue using the system and enhanced quality of life. Practical implications: This study enables managers to evaluate types of policing quality and effectively implement strategies to address security and sustainability issues that exist currently in smart services. Originality/value: Previous studies on policing service quality have not sufficiently addressed the role of smart policing service quality; the nature of discussion in this area is primarily based around concepts. The development of the smart policing service quality scale provides a measurement tool for researchers to use to enhance the understanding of smart policing service quality.